Analysis of Students’ Difficulty in Reading Academic Journal at English Department Universitas Pasir Pengaraian - Juhastri, Azi Nurazima; Eripuddin, Eripuddin; Rahayu, Pipit; Handayani, Sri; Suryani, Risa; Mustika, Feni; Ningsih, Cindy Wahyu; Afisha, Della (Journal of English Language and Education, 2025)
Reading academic journals is essential for English department students, yet many face challenges comprehending them effectively. While numerous studies emphasize the importance of reading skills in academic success, limited research specifically addresses difficulties in reading journals among university students in rural contexts. This study aims to analyze the difficulties faced by English Department students at Universitas Pasir Pengaraian in reading academic journals. A descriptive qualitative method was employed, involving 36 students as the research population. Data were collected through questionnaires and interviews. The findings reveal that the main difficulties include limited vocabulary, unfamiliarity with academic structures, and lack of background knowledge on the journal topics. These issues contribute to reduced comprehension and motivation. The study concludes that targeted reading strategies and academic support are essential to improve students' journal reading competence.